The demographic approach to the quality of official ethnicity data in Serbia - a research proposal - Trnavčević Nevena; Knežević Aleksandar (Stanovništvo)
Demographic studies of the population by ethnicity are gaining new significance. Emigration, intensive aging, and declining fertility have caused changes in demographic trends, particularly in communities of different ethnic backgrounds. Ethnodemographic trends are mostly observed through the lens of official ethnic statistics. The most important factor regarding data quality is the approach towards subjective criteria in the self-declaration of ethnic affiliation in censuses and vital statistical surveys. This paper presents examples of statistical deviations of demographic indicators based on official data on ethnicity and introduces a proposal for research into their quality and use value. Our research proposal is based on previous demographic analyses of ethnicity data and focuses on the demographic framework of statistics of ethnicity in Serbia through data quality analysis. We contend that the results presented in the paper constitute a sufficient argument for a broader methodological discussion regarding the necessity of demographic research into ethnicity data to create a “more objective” demographic picture of minorities. Examining the quality of ethnicity data is very important for analysing indicators of statistically variable minority ethnic groups. The results of the research can form the basis for reviewing the data sources on which policies towards ethnic minorities are formulated.